The impact of immunogenicity on therapeutic antibody pharmacokinetics: A preclinical evaluation of the effect of immune complex formation and antibody effector function on clearance. Issue 1 (1st January 2021) - Opolka-Hoffmann, Eugenia; Jordan, Gregor; Otteneder, Michael; Kieferle, Robin; Lechmann, Martin; Winter, Gerhard; Staack, Roland F.
ABSTRACT: The occurrence of an immune response against therapeutic proteins poses a major risk for the development of biologics and for successful treatment of patients. Generation of anti-drug antibodies (ADAs) can lead to formation of immune complexes (ICs), consisting of drug and ADAs, with potential impact on safety, efficacy and exposure. Here, we focus on the effects of IC formation, i.e., specific IC sizes, ADA and drug properties, on drug pharmacokinetics. Pre-formed IC preparations of an IgG1 drug (with wild type or with an ablated effector function at the Fc domain) and different ADA surrogates (directed against the complementarity-determining regions or Fc domain of the drug) were administered to rats and collected serum was analyzed to determine the total drug concentration. A combination of size-exclusion chromatography and ELISA enabled a size-specific evaluation of IC profiles in serum and their changes over time. Within five minutes, total drug concentration decreased by ~20–60% when the drug was complexed. Independent of the ADA surrogate and drug variant used, increasing IC size led to increased clearance. Comparing ICs formed with the same ADA surrogate but different IgG1 variants, we observed that complexed drug with a wildtype Fc domain showed faster clearance compared to immune effector function modified drug. Data generated in this study indicated that clearance of drug due to ADA generation is driven by size and structure of the formed ICs, but also by the immune effector functions of the Fc domains of IgGs. Abbreviations Ab: antibody, ADA: anti-drug antibody, AUC: area under the curve, Bi: biotin, CDR: complementary-determining region, cmax : maximal concentration, Dig: digoxigenin, ELISA: enzyme-linked immunosorbent assay, Fc: fragment crystallizable, FcRn: neonatal Fc receptor, HMW: high molecular weight, IC: immune complex, IC-QC: immune complex quality control, IgG: immunoglobulin G, mAb: monoclonal antibody, mADA: monoclonal ADA, pAb: polyclonal antibody, pADA: polyclonal ADA, PD: pharmacodynamics; PK: pharmacokinetic, QC: quality control, SEC: size-exclusion chromatography, WT: wildtype